Hubungan antara Dukungan Sosial Suami terhadap Work Family Balance Pada Ibu Bekerja yang Memiliki Anak Usia Dini - Ristianaa, Ema; Bantam, Dian Juliarti (PSIMPHONI, 2024)
Work-family balance is a condition in which individuals can experience satisfaction in fulfilling their roles as both workers and family members. This study aims to analyze the relationship between husband’s social support and work-family balance among working mothers with young children. The research subjects consisted of married working women with children aged 0–6 years. This study employed a correlational quantitative method to examine the relationship between variables. The measurement instruments demonstrated good reliability, with a reliability coefficient of 0.872 for husband’s social support and 0.915 for work-family balance. The results of the analysis indicate a significant positive relationship between husband’s social support and work-family balance among working mothers with young children (r = 0.481, p < 0.01). Husband’s social support contributes 32.9% to work-family balance. Based on these findings, it is recommended that husbands actively provide emotional, instrumental, and informational support to their wives to enhance their ability to balance work and family roles. Additionally, organizations should consider implementing family-friendly policies, such as flexible work arrangements and family support programs, to strengthen work-family balance in the workplace.